Identification of safe and stable operation conditions for pressure retarded osmosis with high performance hollow fiber membrane - Chen, Yunfeng (2016)
Pressure retarded osmosis (PRO) is a promising energy harvesting technique. However, when polymeric hollow fiber membrane is used for the PRO process, the mechanical strength of the membrane is a big concern. As hollow fiber membrane is self-supported and due to its polymeric nature, it may gradually deform over time under high pressure loading, or membrane "creeping" will occur. Current work is the first attempt to analyze the membrane creeping phenomenon of a novel thin film composite (TFC) hollow fiber. The membrane creeping was evaluated via nanoindentation by using atomic force microscope (AFM). A non-stop 200-hour PRO test and integrity check, which have not been reported previously, were carried out to investigate the membrane performance under various operating pressures. The results show that the membrane is able to produce a stable power density output of 19.2W/m2 at 15.0bar, using 1.0M NaCl as the draw solution and DI water as the feed water. Membrane creeping was observed when the applied pressure exceeded the safe operation limit (or the flux turning point, where the membrane flux started to increase with increasing applied pressure in the PRO mode), which caused an irreversible damage to the membranes. This study identified safe and optimum operation conditions of the laboratory-made PRO hollow fiber membrane to achieve the most favorable PRO performance. It provides guidance for practical applications of polymeric hollow fiber membranes in PRO process.